Application of cement-based materials as engineered barriers in geological disposal facilities - Jie Xing; Lianfeng Gao; Zhenguo Zhang; Niangang Luo (Alexandria Engineering Journal)
Cement-based materials are essential components of engineered barrier systems in geological disposal facilities for both hazardous and radioactive waste. This review provides a comprehensive examination of the application of cement-based materials in various aspects of geological disposal. Specifically, it details the use of cement paste backfill for mine tailings, which has shown a reduction in permeability by 95 %, and cementitious grouts for ground stabilization, achieving a compressive strength increase of 20 %. Shotcrete applications for rock support demonstrate enhanced adhesion properties, with a 30 % improvement in bond strength. Cementitious matrices for low- and intermediate-level waste immobilization have been optimized to reduce leachability by 40 %. Concrete containers for high-level waste and spent fuel are discussed, highlighting their ability to maintain structural integrity under high radiation and thermal loads for over 100 years. Cement-based seals for repository closure are also examined, with a focus on their self-sealing properties and long-term durability. The long-term performance of these engineered barriers is influenced by deterioration processes such as physical, chemical, and biological degradation. This review discusses optimization strategies, including the development of alternative binder systems that reduce CO₂ emissions by 30 %, the incorporation of nanoengineered cements that enhance mechanical properties by 25 %, the use of smart additives that provide real-time monitoring capabilities, and the creation of multifunctional composites that combine strength and self-healing properties. Future research directions are highlighted, emphasizing the need for advanced predictive models, innovative material formulations, and integrated monitoring technologies to ensure the long-term safety and performance of geological disposal systems.